A proposal for an alternative class of spin filter materials: Hybridization-induced high-TC ferromagnetic semiconductors CoVXAl (X = Ti, Zr, Hf) - Galanakis, I.; Ozdogan, K.; Sasioglu, E. (AMER INST PHYSICS, 2013)
Using ab-initio electronic structure calculations, we propose an alternative class of spin filter materials (SFMs) based on the quaternary Heusler compounds CoVXAl (X Ti, Zr, Hf). We show that the p-d hybridization leads to the formation of the ferromagnetic band gap with a moderate exchange splitting Delta E-ex and a Curie temperature T-C well above the room temperature. We find that all three compounds are thermodynamically and magnetically stable. Combination of high T-C value together with moderate exchange splitting, as well as crystal structures compatible to the existing semiconductors and metals, makes these compounds promising candidates to find applications as SFMs in spintronics devices. (C) 2013 AIP Publishing LLC.
Keywords: Physics